A prognostic risk model for patients with triple negative breast cancer based on stromal natural killer cells, tumor‐associated macrophages and growth‐arrest specific protein 6. Issue 7 (14th June 2016) - Tian, Wenjing; Wang, Le; Yuan, Lili; Duan, Wenming; Zhao, Wenhui; Wang, Shuhuai; Zhang, Qingyuan
Abstract : The aim of this study was to establish a prognostic risk model for patients with triple negative breast cancer (TNBC). A total of 278 specimens of human TNBC tissues were investigated by immunohistochemistry for growth‐arrest specific protein 6 expression, infiltrations of stromal natural killer cells and tumor‐associated macrophages. According to their prognostic risk scores based on the model, patients were divided into three groups (score 0, 1–2, 3). Correlations of prognostic risk scores, clinicopathologic features and overall survival (OS) were analyzed. To study the clinical value of this stratification model in early disease recurrence or metastasis, 177 patients were screened out for further analysis. Based on disease free survival (DFS), 90 patients fell within the DFS ≤3 years group and 87 patients within the DFS ≥5 years group. We analyzed the differences in prognostic risk scores between the two groups. The prognostic risk scores were negatively related to tumor size, lymph node metastasis and P53 status ( P < 0.001 for all). Patients with low prognostic risk scores had longer OS ( P = 0.001). Using multivariate analysis, it was determined that TNM stage (HR = 0.432, 95% confidence interval [CI] = 0.281–0.665, P = 0.003), FOXP3 positive lymphocytes (HR = 1.712, 95% CI = 1.085–2.702, P = 0.021) and prognostic risk scores (HR = 1.340, 95% CI = 1.192–1.644, P = 0.005) were independent prognostic factors for OS. Compared with the DFS ≥5 years group, the DFS ≤3 years group patients had significantly higher prognostic risk scores ( P < 0.001). In conclusion, the prognostic risk score of the model was a significant indicator of prognosis for patients with TNBC. Abstract : The prognostic risk model showed significant effect on overall survivals of triple negative breast cancer patients. The prognostic risk score of this model was a significant indicator of prognosis for patients with triple negative breast cancer.